A time-warped MDCT approach to speech transform coding - Edler, Bernd; Disch, Sascha; Bayer, Stefan; Fuchs, Guillaume; Geiger, Ralf (126th AES Convention, 2009)
The modified discrete cosine transform (MDCT) is often used for audio coding due to its critical sampling property and good energy compaction, especially for harmonic tones with constant fundamental frequencies (pitch). However, in voiced human speech the pitch is time-varying and thus the energy is spread over several transform coefficients, leading to a reduction of coding efficiency. The approach presented herein compensates for pitch variation in each MDCT block by application of time-variant re-sampling. A dedicated signal adaptive transform window computation ensures the preservation of the time domain aliasing cancelation (TDAC) property. Re-sampling can be designed such that the duration of the processed blocks is not altered, facilitating the replacement of the conventional MDCT in existing audio coders.
UnivIS-Import:2019-03-25:Pub.2009.tech.IE.aulab.zentr.atimew

Enhancement of Coded Speech Using a Mask-Based Post-Filter - Korse, Srikanth; Gupta, Kishan; Fuchs, Guillaume (ICASSP, IEEE International Conference on Acoustics, Speech and Signal Processing - Proceedings, 2020)
The quality of speech codecs deteriorates at low bitrates due to high quantization noise. A post-filter is generally employed to enhance the quality of the coded speech. In this paper, a data-driven post-filter relying on masking in the time-frequency domain is proposed. A fully connected neural network (FCNN), a convolutional encoder-decoder (CED) network and a long short-term memory (LSTM) network are implemeted to estimate a real-valued mask per time-frequency bin. The proposed models were tested on the five lowest operating modes (6.65 kbps-15.85 kbps) of the Adaptive Multi-Rate Wideband codec (AMR-WB). Both objective and subjective evaluations confirm the enhancement of the coded speech and also show the superiority of the mask-based neural network system over a conventional heuristic post-filter used in the standard like ITU-T G.718.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Deep Neural Network; Post-filtering; Speech Coding; Speech Coding Enhancement